2019
DOI: 10.1101/846022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laminin-511 and α6 Integrins Regulate the Expression of CXCR4 to Promote Endothelial Morphogenesis

Abstract: AbstractDuring angiogenesis, endothelial cells engage components of the extracellular matrix through integrin-mediated adhesion. Endothelial expression of laminin-411 and laminin-511 are known to promote vessel stability. However, little is known about the contribution of these laminins to endothelial morphogenesis. We used two organotypic cell culture angiogenesis assays in conjunction with RNAi approaches to demonstrate that depletion of either the α4 chain of laminin-411 or … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 57 publications
(50 reference statements)
1
13
1
Order By: Relevance
“…We showed that α6 integrins promoted migration, the expression of their substrate, laminin-511, as well as the angiogenesis-associated genes angiopoitin-2 (ANGPT2) and the chemokine receptor, CXCR4. We further demonstrated that recombinant CXCR4 partially rescued endothelial morphogenesis when the expression of α6 integrins was inhibited (Xu et al, 2020). However, our previous studies did not distinguish contributions from α6β1 or α6β4 or whether the α3β1 laminin-binding integrin also contributes endothelial morphogenesis in these models.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…We showed that α6 integrins promoted migration, the expression of their substrate, laminin-511, as well as the angiogenesis-associated genes angiopoitin-2 (ANGPT2) and the chemokine receptor, CXCR4. We further demonstrated that recombinant CXCR4 partially rescued endothelial morphogenesis when the expression of α6 integrins was inhibited (Xu et al, 2020). However, our previous studies did not distinguish contributions from α6β1 or α6β4 or whether the α3β1 laminin-binding integrin also contributes endothelial morphogenesis in these models.…”
Section: Introductionmentioning
confidence: 63%
“…Using HUVECs, we previously demonstrated that α6 integrins promote endothelial morphogenesis, in part by promoting cell migration, as well as the expression of CXCR4, ANGPT2, and the α5 chain (LAMA5) of laminin-511 (Xu et al, 2020). However, we did not determine the specific contributions of α6β1 and α6β4.…”
Section: Integrin α6β4 Promotes Endothelial Migrationmentioning
confidence: 72%
See 3 more Smart Citations